Trends in Head and Neck Cancer in Saudi Arabia from 2016–2020 - Homeida, Lujain (Journal of Contemporary Medical Sciences, 2025)
Objectives: Head and neck cancer (HNC) is considered the seventh most common cancer worldwide. To evaluate the incidence and geographical distributions of head and neck cancer among the Saudi population in a specific period. Methods: A retrospective and a descriptive study investigating HNC in Saudi population from January 2016 through December 2020 was conducted based on data obtained from the Saudi Cancer Registry SCR. Male and female data were included on lip, tongue, mouth salivary glands, oropharynx, nasopharynx hypopharynx, pharynx, nose and sinuses, and larynx. Age-standardized rate (ASR) and age-specific incidence rate (AIR) were calculated with a focus on age, gender and regional differences. Results: The total number of HNC cases identified by the SCR was 3,232 cases in which males were 2082 (64.4%) and females were 1,150 (35.5%). The mean ASR per 100,000 of HNC was higher in males at 4.94 compared to females at 2.9 over the study period. The mean ASR per 100,000 population ranged from 2.22 in Hail to 5.3 in Jazan, with a national average of 3.68 per 100,000. Positive correlation between HNC incidence and age was noted. Nasopharyngeal cancer showed the highest number of cases for both genders through the same period. Conclusion: Between 2016 and 2020, HNC incidence in Saudi Arabia remained stable, with consistently higher ASR in males. These findings highlight the importance of targeted, region-specific health initiatives, greater public education, and age-targeted screening to reduce the impact of HNC in Saudi Arabia.